Perilaku Petani Terhadap Penerapan Teknologi Tepat Guna Dalam Pengolahan Kopi Arabika Kintamani (Studi Kasus Desa Mengani, Kecamatan Kintamani, Kabupaten Bangli, Provinsi Bali) - ARIEZONA, PAMULA CARAKA NEGARA; SARJANA, I MADE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
The Farmers Behavior of the Application of Appropriate Technology in Kintamani Arabica Coffee Cultivation (Case Study of Mengani Village, Kintamani District, Bangli Regency, Bali Province).  The purpose of the study was to analyze farmers behavior of the application of appropriate technology in processing Kintamani Arabica coffee. The research method in this study used a saturated sampling technique or census. The types of data used are quantitative data and qualitative data, as well as primary and secondary data sources. Methods of data collection using interviews, observation and documentation studies. The data analysis method used descriptive analysis. The results showed that farmers' perceptions of the application of appropriate technology in processing Kintamani Arabica coffee still had problems with the wet-processed coffee processing method, and there were things that were conveyed that had not been accepted and applied by farmers during counseling and required confidence in the farmers that this -This new thing will come in handy. The recommended suggestion is that Arabica coffee farmers in Mengani Village are advised to review and re-evaluate the application and implementation of appropriate technology using wet processing methods in processing Kintamani Arabica coffee.